De morbis (Practica) puerorum atribuido a Gordonio (siglo XV): análisis comparativo entre Vaticanus Latinus 10213, fol. 541r(a-b) y Ms. Sloane 71, fols. 81r-83v - Domínguez Rodríguez, María Victoria; Rodríguez Herrera, Gregorio (2021)
This paper presents an analysis and comparative study between the Latin version of De morbis (Practica) puerorum ( Vaticanus Latinus 10213) and one of its Middle English translations (Ms. Sloane 71). It aims at establishing the extent to which both texts depend on each other, considering that, even though attributing them to his authorship could be a strategy to achieve auctoritas , there is also some evident interference from other works by Gordon. We also include a transcription of the Middle English translation, since it has so far gone unnoticed for scholars of this medieval doctor.
Este artigo, baseado na análise e estudo comparativo entre a versão latina de De morbis (Practica) puerorum (Vaticano Latinus 10213) e uma tradução para o Inglês Médio (Ms. Sloane 71) estabelece o grau de dependência entre ambos os textos, a autoria de Gordónio como estratégia para dotar o texto de auctoritas, bem como a interferência de outras obras de Gordónio na tradução. Também oferece uma transcrição da tradução, dado que, até agora, ela tem passado despercebida aos estudiosos deste médico medieval.
Keywords: Mercuriale, Girolamo, -- 1530-1606; Medicina